(untitled) (Research, Society and Development, 2021)
The bovine lung, considered as viscera, is often disposed of inappropriately in the environment. However, this organ stands out for having high levels of iron and proteins with high biological value. Therefore, the aim of the current study was to develop a product enriched with bioavailable heme iron. Hamburger formulations were prepared with different concentrations of bovine lung. In these products, the chemical composition and the iron content were determined. The samples were evaluated sensorially by affective acceptance test and purchase intention test. The data obtained were analyzed using analysis of variance and compared using the Tukey test (p <0.05). The hamburgers produced with different concentrations of lung presented mostly water (67.9-68.16%), proteins (18.16-19.05%) and lipids (8.09-8.31%). The content of bioavailable heme iron varied between 9.23 and 14.03 mg / 100g in the samples, being approximately three times higher in the sample with 100 g of lung, compared to the control sample. Hamburgers formulated with the addition of bovine lung were accepted by the participants (AI> 70%) and had high percentages of purchase intent (>82%). The product can be considered a promising alternative for the intake of iron and essential aminoacids, which can help in the fight against anemia and reduce the consequences caused by this deficiency in the human body, such as a deficit in motor and cognitive development.